Angiolymphoid hyperplasia with eosinophilia as simultaneous cutaneous and vascular lesions with radial artery aneurysm - Guevara-Noriega, Kerbi Alejandro; Zapata, Jairo Andres; Szczesna, Monika; Guevara-Noriega, Uvanys Rafael; Solano, Albert; Ares-Vidal, Jesus (International Surgery Journal, 2016)
Among the primary vascular neoformative processes is the angiolymphoid hyperplasia with eosinophilia (ALHE), rare and of endothelial origin with variable clinical presentation. We report an unusual presentation of ALHE, with both cutaneous and vascular lesions in the upper extremity, vascular lesion associated with radial artery aneurysm. A Male, 33 year-old with 6 months history of painless, erythematous and violaceous papule in upper extremity. No history of trauma or infection. Eosinophilia of 1.12 x 10^3/uL. Negative serology of HHV8. Radiological imaging showed three similar solid lesions in forearm. One lesion was in contact with the radial artery, which presented aneurysmal dilation. Arteriography demonstrates radial artery aneurysm. The lesion biopsy was performed and exhibited morphological and immunocytochemical features compatible with ALHE. Surgical resection and bypass between brachial artery and radial artery distal to the lesion with inverted saphenous vein was performed. Histopathological and immunocytochemical study of the lesions confirmed the diagnosis. Our most interesting finding was the presence of multiple lesions in the upper extremity, which appeared as cutaneous and vascular lesions. The latter appeared as a vascular tumor with aneurismal dilatation of the radial artery. Our case highlights attention reporting simultaneous presentation of skin lesions and vascular lesions in the extremities, showing a spectrum of ALHE may be broader than known so far. Its etiology and long-term outcomes is still unknown. This puts the ALHE as differential diagnosis in cases of pulsatile cutaneous lesions and highlights the utility of radiological imaging and histopathological and immunocytochemical study.